2017
DOI: 10.1038/onc.2017.213
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Loss of BRCA1 or BRCA2 markedly increases the rate of base substitution mutagenesis and has distinct effects on genomic deletions

Abstract: Correction to: Oncogene (2017) 36, 746–755; doi:10.1038/onc.2016.243; published online 25 July 2016 In Figure 2c, the label above the middle panel in this paper was published incorrectly. The correct label should read BRCA1−/− instead of BRCA2−/−. The corrected figure 2 is below. The publishers wishto apologise for any inconvenience caused.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Analysis of the mutational spectra of nucleotide triplets in tumor specimens found that a signature characterized by a flat mutational spectrum (Signature 3) was connected to HRD; thus, the relative contribution of the corresponding mutational process might be used as an estimator for the deficiency. The relative proportion of deletions caused by microhomology-mediated end joining can also be used as a robust estimator for HRD [ 12 ]. All these mutational signatures together with the so-called rearrangement signatures were combined into a robust logistic-regression model, called HRDetect [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the mutational spectra of nucleotide triplets in tumor specimens found that a signature characterized by a flat mutational spectrum (Signature 3) was connected to HRD; thus, the relative contribution of the corresponding mutational process might be used as an estimator for the deficiency. The relative proportion of deletions caused by microhomology-mediated end joining can also be used as a robust estimator for HRD [ 12 ]. All these mutational signatures together with the so-called rearrangement signatures were combined into a robust logistic-regression model, called HRDetect [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have identified a "BRCAness" signature that is associated with HR-deficient cancers, commonly referred to as Signature 3 in the Catalog of Somatic Mutations in Cancer (COSMIC). Signature 3 is characterized by an elevated number of base substitutions, deletions, and insertions > 3 bp with microhomologies located at the suspected breakpoint junctions, characteristic of alt-EJ repair [114].…”
Section: Error-prone Repair Contributes To Genome Evolution In Cancermentioning
confidence: 99%
“…Germline mutations in the BRCA1 gene occurring in breast cancer cases often result in a complete loss of function of BRCA1 [134,135]. In turn, BRCA1 loss is synthetically viable with the loss of tumor protein p53-binding protein 1 (TP53BP1) [136].…”
Section: Critical Role Of Brca1 and Tp53bp1 In Vd3 Signaling In Triplmentioning
confidence: 99%